Biochemical status of feral honey bees (Apis mellifera) infested with various pathogens. Issue 5 (20th October 2017) - Łopieńska-Biernat, Elżbieta; Sokół, Rajmund; Michalczyk, Maria; Żółtowska, Krystyna; Stryiński, Robert
Abstract : Feral bees colonizing large forest habitats without human intervention are also affected by diseases. Infected bees that survive several seasons constitute an interesting object of scientific inquiry. Little is known about the health and status of feral honey bee populations. The pathogens infesting/infecting bee colonies and the biochemical status of unhealthy bees need to be studied to prevent the global decline in bee populations. Honey bees inhabiting hollow trees in forest reserves of north-eastern Poland, infected with Nosema ceranae or infested with Varroa destructor and/or infected with the deformed wing virus (DWV), were analyzed. Differences in the analyzed biochemical parameters were noted in groups infected/infested with various pathogens relative to the control group. The most significant variations were observed in antioxidant parameters: lower total antioxidant status (TAS) (excluding group N. ceranae ), lower activity of superoxide dismutase (SOD) and peroxidase (POX) (excluding group N. ceranae  + DWV), higher activity of glutathione transferase (GST), and higher glutathione (GSH) levels in groups infected with N. ceranae. Glycogen concentration was higher in DWV-infected bees. In comparison with bees infested with V. destructor only, co-infested groups were characterized by fluctuations in carbohydrate concentration, subject to the co-infesting pathogen. The presence of a single pathogen has a less detrimental effect on most metabolic parameters in feral honey bees than concomitant infections with several pathogens. The results of this study suggest that co-infestations with V. destructor and DWV in feral honey bees have more serious consequences than co-infections with Nosema sp. and DWV.